A Postprocedure Wrap‐up Tool for Improving OR Communication and Performance. (4th January 2018) - Norton, Rebecca; Mordas, Dolores
Abstract: In 2015, perioperative nursing staff members at a community hospital designed and implemented a tool to help improve communication and performance. Our postprocedure wrap‐up tool and its follow‐up process have allowed us to achieve improvements in both efficiency and staff member satisfaction. By implementing a process to document problems as they occur and quickly transmit information to the staff members who are best able to correct these issues, we greatly improved our workflow. Furthermore, by inputting information into spreadsheets using problem codes, thereby replacing anecdotal information with hard data, we targeted areas that needed improvement and used that information for budget planning, training, and allocating resources. Enlisting the input of all members of the surgical team allowed us to identify the root causes of issues that interfered with the staff members' ability to provide efficient, safe, and reliable patient care.